Implikasi Penerapan Undang-Undang Cipta Kerja Terhadap Pelaksanaan Administrasi Pemerintah - Doharman Lumban Tungkup; Fadjrin Wira Perdana; Irwan Irwan; Surnata Surnata; Wahyudi Siswanto (CV. Publikasi Indonesia, 2022)
Indonesia as a state of law, it is not surprising that the issuance of new laws is often carried out, either through laws, regulations, regional regulations or other things. One of the hotly discussed regulations is the Job Creation Act. The existence of the job creation law certainly provides changes to the previously applicable regulations so that the government must be able to adapt quickly. For this reason, this research was conducted to determine the implications of the implementation of the Job Creation Act on the implementation of government administration. The research approach used is qualitative with a normative juridical type, namely through a literature review. In addition, data collection techniques are also through interviews, observation and distributing questionnaires to selected respondents through purpose sampling techniques. The result of this research is that the implementation of the Job Creation Act has implications for the implementation of government administration, specifically in the areas of authority, discretion, electronic decisions, and positive fictitious.